Impact of Information and Communication Technology on the Performance of Deposit Money Banks in Nigeria - Peace, Nwakoby Nkiru; Sidi, Charity Philip; Abomeh, Ofobruku Sylvester (International Journal of Management and Sustainability, 2018)
The study examines the impact of information and communication technology on the performance of deposit money banks in Nigeria between the periods 2006 to 2015. The log-linear regression model was used to test the impact of various forms of information and communication technology on the banks return on equity (ROE), the computation of the result was done using the econometric computer software package, e-view version 8.0. The result shows that the adoption of various forms of information and communication technology has greatly influenced the quality of banking operations, performance and has specifically increased banks return on equity. Information and communication technology usage can sustain returns on equity of deposit money banks in the long run. The study recommends that investment in information and communication technology should form an important component in the overall strategy of banking operation, as these will make Nigerian banks to be more efficient, profitable, and competitive.